Phytochemical Screening and Activity Test of Antioxidant Ethanol Extract of Buni Leaves (Antidesma bunius L. Spreng) Using DPPH Method - Dewa Ayu Puspaning Kumaradewi; Windah Anugrah Subaidah; Yayuk Andayani; Ali Al-Mokaram (Jurnal Penelitian Pendidikan IPA, 2021)
Research on phytochemical screening and antioxidant activity testing of the ethanol extract of buni leaves (Antidesma bunius L. Spreng) has been carried out. This study aims to identify secondary metabolite compounds contained in buni leaf plants to see the activity of the ethanol extract of buni leaves using the DPPH method. Buni leaves were extracted in 96% ethanol by maceration method, then evaporated using a rotary evaporator. The results of thick extract were screened for phytochemicals such as phenolics, tannins, flavonoids, saponins, alkaloids, steroids and terpenoids using a qualitative color test method and carrying out antioxidant activity using a UV-Vis spectrophotometer with Vitamin C as a comparison. The results showed that the ethanol extract of buni leaves contained phenolic compounds, tannins, flavonoids, saponins, alkaloids, steroids and terpenoids as well as IC50 Vitamin C of 5.22 ppm which is classified as a very strong antioxidant, while the IC50 of buni leaves ethanol extract is lower at 61, 8 ppm which is classified as a strong antioxidant